Competitive changes and innovation practice: Analysis of R&D policy on the Brazilian electricity sector - Artur Tavares Vilas Boas Ribeiro; Guilherme Soares Gurgel do Amaral; Mario Sergio Salerno; Guilherme Ary Plonski; Eduardo Zancul (Next Energy, 2024)
The electricity sector is in the midst of structural changes accelerated by current trends such as digitalisation, decarbonisation, and decentralisation. This phenomenon led companies to explore new ways of innovating. However, some experts and practitioners argue that the current R&D regulation may limit strategic advancements. This paper aims to analyse the current R&D policy on the electricity sector in light of digital innovation efforts. The study focuses on the Brazilian regulatory framework for R&D activities, which has been evolving since the early 1990s. Therefore, the study presents a multiple case analysis of different projects aimed at innovation through digitalisation, highlighting the main bottlenecks and their relationships with the regulatory structure. The paper contributes by presenting a timeline of R&D regulatory changes within the Brazilian electricity sector, discussing the recent innovation movements, and detailing an organised structure on regulatory constraints and practical consequences, which could be useful when developing new policies and practices on innovation for energy sectors.